OPTIMIZATION OF RESOURCE POTENTIAL OF THE ENTERPRISE ON THE BASIS OF ANALYSIS OF THE STRUCTURE OF FINANCIAL RESOURCES - Oleksandr Gerasimchuk (Izdevnieciba "Baltija Publishing", 2021)
The subject of research of the scientific article is the optimization of the resource potential of the enterprise based on the analysis of the structure of financial resources. The methodological basis of the study were the provisions of modern economic theory, financial statements of the studied enterprise and scientific works of scientists. The purpose of the study is to analyze the optimization of the components of the resource potential of the enterprise. In the course of the research the estimation of optimization of structure of financial resources of the enterprise on the basis of the multicriteria approach was carried out. It is determined that the total amount of financial resources that is necessary for the researched enterprise - sources of financing is 150 000 thousand UAH. Based on the results of calculations of the cost of borrowed capital, taking into account the tax corrector, the weighted average cost of capital was calculated for all 10 alternatives. Given that the company is interested in obtaining a certain amount of financial resources at the lowest weighted average interest rate in the presented models, the best alternatives are 1 and 10 where the weighted average cost of capital is 15.51%. It is concluded that under the terms of the settlement agreement a significant increase in the profitable part of the researched enterprise is planned, taking into account the possibilities in the future, and first of all taking into account the real, for today, state of financial and economic activity of the enterprise. Therefore, the company needs to use a comprehensive approach to managing its financial resources. In the conditions of transformation of market relations forecasting and substantiation of strategy of development of financial and economic activity of the organization taking into account an estimation of dynamics of a market conjuncture and influence of macroeconomic factors of maintenance of conformity of volume and structure of own and involved financial resources (capital). Resources in the process of operational, investment, financial activities of the organization to achieve optimal structure and value of own and borrowed resources from the standpoint of impact on the financial condition of the enterprise and ensure its financial stability, liquidity, solvency minimization of financial resources.